2022
DOI: 10.1111/sms.14242
|View full text |Cite
|
Sign up to set email alerts
|

The load borne by the Achilles tendon during exercise: A systematic review of normative values

Abstract: The Achilles tendon (AT) can be exposed to considerable stress during athletic activities and is often subject to pathologies such as tendinopathies. When designing a prevention or rehabilitation protocol, mechanical loading is a key factor to consider. This implies being able to accurately determine the load applied to the AT when performing exercises that stress this tendon. A systematic review was performed to synthesize the load borne by the AT during exercises/activities. Three databases (Pubmed, Embase a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 75 publications
2
9
0
Order By: Relevance
“…Estimates of peak AT force ranging from 8.2–10.1 body weights (bw) for speeds of 2.68–4.47 m·s −1 in this study were within the range of those reported in literature (5). Estimates of peak AT force via musculoskeletal modeling range from 5.2–5.4 bw while running at 2.9 m·s −1 (3,25) to 4.2–6.6 bw at 3.4–3.7 m·s −1 (26–30) to 7.4 bw at 4.8 m·s −1 (30).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Estimates of peak AT force ranging from 8.2–10.1 body weights (bw) for speeds of 2.68–4.47 m·s −1 in this study were within the range of those reported in literature (5). Estimates of peak AT force via musculoskeletal modeling range from 5.2–5.4 bw while running at 2.9 m·s −1 (3,25) to 4.2–6.6 bw at 3.4–3.7 m·s −1 (26–30) to 7.4 bw at 4.8 m·s −1 (30).…”
Section: Discussionsupporting
confidence: 89%
“…Previous studies have identified how the loading experienced by the AT can affect running economy (1), influence the risk of developing overuse injuries (2), and aid in designing appropriate rehabilitation programs following AT rupture (3). Forces are traditionally estimated using laboratory-based motion analysis and electromyography data in conjunction with complex musculoskeletal models (4,5). It is often desirable to understand force generation outside of the laboratory or clinic to capture the natural movements and environments that people experience during daily life, work, or sports.…”
mentioning
confidence: 99%
“…Although the current study is the first one to report Achilles tendon loading in patients with AT, comparing our healthy participants to previous literature, peak loading results for walking and variations in heel drop and heel rise exercises fall within the range previously observed (42). However, we did find lower peak loading for lunge and squat exercises, 3.2BW ± 0.7BW and 2.1BW ± 0.6BW respectively, compared to Baxter et al (9) with peak loading of 2.1BW ± 0.6BW for lunge and 1.1BW ± 0.3BW for squat.…”
Section: Discussionsupporting
confidence: 78%
“…We considered the Achilles tendon pull to be the most significant force to cause failure of fixation for this study, although, in actual trauma, Achilles tendon pull is not the sole cause of the failure. An Achilles tendon can be subjected to up to 3.95 times of body weight force during walking, and the force can be increased up to 7.71 times of body weight during running [ 22 ]. In a non-weight-bearing position, ankle plantar flexion can generate 200 N of force at the Achilles tendon; bilateral legs standing ankle plantar flexion can generate 1251 N; and the force can increase to 2760 N in a single-leg stance ankle plantar flexion [ 23 ].…”
Section: Discussionmentioning
confidence: 99%